2021
DOI: 10.1037/ebs0000230
|View full text |Cite
|
Sign up to set email alerts
|

Further support for the role of heroism in human mate choice.

Abstract: for collecting part of the data for this study. We also thank Catherine Salmon for handling our manuscript and the two anonymous reviewers for their time and valuable comments throughout the peer review process. Author contributions: MSB formulated the project, designed the experiment and collected the data. JB conducted all analyses. MSB and JB wrote the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…If this is indeed why prosociality is important in mate choice, then what psychological characteristics that are beneficial in partners and parents are being signalled by the prosocial actor to potential partners? Research has explored different forms of prosocial behaviour, such as heroism (Bhogal & Bartlett, 2020;Margana et al, 2019), trustworthiness (Ehlebracht et al, 2018) and fairness . These studies have shown consistencies in terms of the desirability of prosocial behaviours (again, particularly for long-term relationships) but also differences in terms of the types of the behaviour and of the context in which it can occur.…”
Section: Further Investigation Of the Role Of Prosocial Behaviours In...mentioning
confidence: 99%
“…If this is indeed why prosociality is important in mate choice, then what psychological characteristics that are beneficial in partners and parents are being signalled by the prosocial actor to potential partners? Research has explored different forms of prosocial behaviour, such as heroism (Bhogal & Bartlett, 2020;Margana et al, 2019), trustworthiness (Ehlebracht et al, 2018) and fairness . These studies have shown consistencies in terms of the desirability of prosocial behaviours (again, particularly for long-term relationships) but also differences in terms of the types of the behaviour and of the context in which it can occur.…”
Section: Further Investigation Of the Role Of Prosocial Behaviours In...mentioning
confidence: 99%
“…That no difference between these acts were found suggests that there is nothing 'special' or 'higher' about the increased risks attributed to heroism as a signal in mate choice, and that these are perceived the same as other altruistic acts. Furthermore this suggests that previous research that has found higher desirability for heroism (e.g., Bhogal & Bartlett, 2021) over altruism may be due to other confounding traits that were signalled by using more extreme and heightened forms of heroism. In other words, when heroism is seen as being desirable, it may not be due to the prosocial or altruistic nature of such acts per se, but because of other desirable traits it also signals, such as physical strength or status.…”
Section: Discussionmentioning
confidence: 85%
“…Materials & Procedure (a) Scenarios Six scenarios were developed based on previous literature (see Bhogal & Bartlett, 2021;Margana et al, 2019) that presented an everyday event, and included descriptions of how two hypothetical target individuals behaved in response. Of these two targets, one behaved in a heroic manner and the other in an altruistic manner.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations